Comparison of Spot Urinary Protein Creatinine Ratio and 24 hour Urinary Protein Excretion in Children presenting with Nephrotic Syndrome in Tertiary Care Hospital of Eastern Nepal - Giri, Arun; Yadav, Sunil Kumar; Shah, Vijay Kumar; Niraula, Niraj; Rauniyar, Anand (Birat Journal of Health Sciences, 2023)
Introduction: Nephrotic syndrome is an important chronic disorder in children and it’s one of the important diagnostic criteria is presence of heavy proteinuria (> 40 mg/m2/hour).As 24-hour urinary protein estimation is cumbersome, inconvenient, time consuming and expensive, a more convenient and accurate method of urinary protein estimation is needed.24-hour urinary protein estimation and urine protein/creatinine in a child with nephrotic syndrome correlates well but there are very few studies done in Nepal to prove this correlation. Hence, this study is undertaken with objective of evaluating usefulness of urine protein/creatinine (UP/UC) in random sample of urine as a rapid and reliable test for quantification of proteinuria and to know their correlation with 24hour urinary protein excretion.Objectives: Primary Objective: To evaluate accuracy of urine protein creatinine ratio (UP/UC) in early morning sample in comparison with 24 hours urinary protein excretion in children of nephrotic syndrome having normal Glomerular Filtration Rate.Secondary Objective:• To evaluate usefulness of urine protein / creatinine ratio (UP/UC) in random sample of urine as rapid and reliable test for quantification of proteinuria.• To evaluate biochemical and other laboratory abnormalities in children with nephrotic syndrome.• To study varied clinical presentation of Pediatric nephrotic syndromeMethodology: This is a descriptive cross-sectional study conducted in pediatric unit, Nobel Medical College Teaching Hospital,  Biratnagar for 12 months. In this study, 50 patients of both sexes, ranging from one to fifteen years of age were studied. The modes of presentation, laboratory investigation reports which included urine routine microscopy, 24-hour urine protein estimation, urine protein / creatinine in random sample of urine were documented and data was analyzed by linear regression.Results: Linear regression revealed that as timed 24-hour urine protein in gm/24 hour increased, Random urine/protein creatinine ratio mg/mg also increased linearly with correlation coefficient of r = 0.56 which was highly significant (p < 0.001).Conclusion: This study concludes that UP/UC ratio in a spot urine reflects the amount of protein in 24-hour urine collection. UP/UC ratio > 2 in patients with normal renal function represents nephrotic range proteinuria.